Relationship of Distribution Seagrass Species with Dugong (Dugong dugon) Sighting at Liki Island-Papua - Aditya Hikmat Nugraha; Ilham Antariksa Tasabaramo; Udhi E Hernawan; Susi Rahmawati; Andri Irawan; Juraij Juraij; Muta Ali Khalifa; I Wayan Eka Dharmawan; Risandi Dwirama Putra; Devia Hartono Puteri (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2019)
Dugong dugon is a herbivorous marine mammal. One of Dugong's favorite foods is seagrass. This study examines the distribution of seagrass species to dugong sighting in Liki Island. The study was conducted in November 2018. Observation of seagrass conditions was carried out using a line transect method and a 50x50 cm transect with a distance interval between 10 m plots. Interviews were also conducted with the community to find out the location of Dugong presence in Liki Island. There are seven species of seagrass found in Liki Island :Enhalus acoroides, Cymodocea rotundata, Thalassia hemprichii, Halophila ovalis, Halodule uninervis, Halodule pnifolia and Syringodium isoetifolium spread over four observation stations. The results showed that Dugong in Liki Island is often found during the eastern season, they often appear in seagrass ecosystem area to do eating activities. Dugong is often found in the eastern part of Liki Island (Station 4) and sometimes also found in the western part of Liki Island (Station 3).Keywords:biodiversity,Dugong dugon, liki, papua, seagrass